The effect of W dopants on the physical and optical properties and photocatalytic activity of ZnO synthesized by the co-precipitation method - Junkrajang Wattana; Maneerat Songpanit; Thanaphon Kansaard; Jirayu Tachaworakit; Thinnasit Thanathaninruj; Chatpong Bangbai; Wanichaya Wanichaya (Thai Journal of Nanoscience and Nanotechnology, 2025)
Due to the wastewater crisis, tungsten (W)-doped ZnOparticles were synthesized with varying W dopant concentrations using the co-precipitation method for the enhancement of photocatalysis application, which can reduce the wastewater crisis by the degradation of pollutant molecules occurring during its process. The crystalline and optical properties of the synthesized powders were analyzed by various methods, as well as their photocatalytic performance. Among all conditions, the WZ-5 sample exhibited the lowest band gap energy at 3.11 eV and the highest photocatalytic efficiency, achieving 98.16% degradation within 60 minutes. These results demonstrate that tungsten doping can effectively enhance ZnO photocatalytic activity by promoting better charge carrier separation and extending light absorption, especially in the visible region, making W-doped ZnO a promising material for wastewater treatment applications
Keywords: ZnO doping and properties